Inflation dynamics and forecast: Frequency matters - Manuel Mota Freitas Martins; Fabio Verona (Bank of Finland, 2021)
Policymakers and researchers see inflation characterized by cyclical fluctuations driven by changes in resource utilization and temporary shocks, around a trend influenced by inflation expectations. We study the in-sample inflation dynamics and forecast inflation out-of-sample by analyzing a New Keynesian Phillips Curve (NKPC) in the frequency domain. In-sample, while inflation expectations dominate medium-to-long-run cycles, energy prices dominate short cycles and business-to-medium cycles once expectations became anchored. While statistically significant, unemployment is not economically relevant for any cycle. Out-of-sample, forecasts from a low-frequency NKPC significantly outperform several benchmark models. The long-run component of unemployment is key for such remarkable forecasting performance.
URN:NBN:fi:bof-202106081279
Keywords: C53; E31; E37; 330; inflation dynamics; inflation forecast; New Keynesian Phillips Curve; frequency domain; wavelets